Tailor-made biofuel-diesel blends properties validation and engine performance - Mohidin, Khairunnisa (2014)
Biofuel-diesel blend offers a great opportunity in reducing the usage of petroleum based diesel and improving the pollutant emission. This study is carried out to perform engine performance testing using a set of fuel blends generated through computational work by Narayanasamy et al.(2014), the blends, content mixture of ethanol(E), butanol(B) and butyl levulinate(BL) with B5 diesel as baseline fuel. The basic properties of the fuel blends were measured according to the corresponding ASTM test method. In the previous work mentioned, Kay’s mixing rule is used for predicting density, distillation temperature, cetane number and calorific value, while an Arrhenius mixing rule is used for viscosity. The results of prediction are then validated by calculating the absolute average deviations(AAD), with the ASTM test. A high AAD obtained for viscosity (31.15%), showing a poor agreement in the prediction model for this property. The lower AAD value obtained for the other tested properties demonstrating the suitability of the used mixing rules. Engine tests on the fuels were carried out on a HINO H07C diesel engine by varying speed in the range of 1200-2400 rpm. The results shows brake specific fuel consumption(BSFC) of the blends was found to be higher than B5 fuel, while a decreasing trend in horsepower produced was observed with increasing speed. The overall observation of emission analyzed gases of CO2, CO, NOx and hydrocarbon(HC), the fuel blends showed a good reduction as compared to the B5 fuel baseline. Blend 2 which consists only the mixture of butanol was found significantly high for HC emission compared to the other blends. It is concluded that Blend 1 (0.746%B5- 0.244%B- 0.010%BL) gave better engine performance with lower BSFC for the same power output compared to the other blends. On the other hand, Blend 3 (0.757%B5- 0.123%B- 0.10%E- 0.02%BL) gives the best overall results in emission reduction among all the fuel blends.